Exploring the nutritional potential of Timru: A dry-land fruit - Mishra, D S; Singh, A K; Apparao, V V; Samadia, D K (Indian Horticulture, 2023)
Timru, a minor forest produce, is endemic to the central India. It is found growing in abundance all over the central parts of India. Commercially, its leaves are used for making bidi, a traditional cigarette. However, most of its produce goes waste since its fruit has never been explored for its nutritional values whereas its fruits are rich in sugars, vitamin C and β-carotene. In addition to this, fruit pulp is also rich in nutrients such as potassium (285.17-304.85 mg/100 g), calcium (375.23-395.35 mg/100/g) and phosphorus (153.40-160.52 mg/100 g). Thus, it is an ideal indigenous fruit for processing into health promoting products like nectar, jam, toffee and squash.